Chlamydia trachomatis infection in infants: a prospective study. Issue 4 (April 1989) - Preece, P M; Anderson, J M; Thompson, R G
Abstract : In a prospective study of Chlamydia trachomatis infection in pregnancy, 198 mothers positive for chlamydial antigen were identified; the infants of 174 were followed for up to six months and C trachomatis was recovered in cell culture from 43 infants (25%). Conjunctivitis occurred in significantly more infants who were positive for C trachomatis (20 of 43, 47%) than in those who were negative (18 of 131, 14%). There were also significantly more lower respiratory tract infections among infants with positive cultures (six of 43, 14%, compared with three of 131, 2%). The chlamydial antigen enzyme linked immunosorbent assay (ELISA) was positive in 61 of 131 infants from whom C trachomatis was not recovered in cell culture. False positive results were usually associated with the isolation of Staphylococcus aureus from samples of pharyngeal aspirate. Our results confirm that C trachomatis infection is a common cause of neonatal conjunctivitis, and respiratory infection in the first few months of life, with an incidence of 8.2/1000 live births. Because the infection is easily treated by oral erythromycin, however, screening during pregnancy is not warranted.